Theory's Children; or, The New Relevance of Musicology - McClatchie, Stephen (Canadian University Music Review / Revue de musique des universités canadiennes, 2000)
The recent theoretical turn in musicology has made the discipline more relevant, both within the university itself, and in the larger society within which it is situated. I consider what this development may mean for younger scholars, both as graduate students and as new faculty members, and explore the paradox that critical theory is often attacked for its impenetrability, yet has allowed us to communicate more easily with our colleagues in other disciplines. Finally, I argue that the primary aim for music study in the twenty-first century should be an ethical one: the creation of whole, musical human beings, literate in, and accustomed to thinking about, musics, plural, rather than Music.